071 Neuropsychological effects of sleep disturbance in healthy subjects. Issue 3 (9th February 2012) - Moriarty, A; Anderson, K; Gallagher, P; McAllister-Williams, R H
Abstract : Background: Cognitive impairment is a major source of morbidity in mood disorders. Sleep disturbance affects 90% of patients with these disorders and remains an under-researched, potentially significant contributor to these common cognitive deficits. Aims: To investigate the association between sleep disturbance and the cognitive functions commonly impaired in mood disorders. Methods: Subjective and objective parameters of sleep quality were measured using questionnaires and an overnight sleep study in 21 healthy male subjects. Subjects were then tested using a battery of neuropsychological tasks designed to measure cognitive domains known to be impaired in mood disorders. Bivariate correlation analysis was used to investigate the association between sleep parameters and neuropsychological function. Results: Lack of variability in physiological sleep measures limited the power to detect correlations between these and cognition. However, a significant correlation (Spearman=0.44, p=0.047) was found between Pittsburgh Sleep Quality Inventory score and error rate in tasks of spatial working memory (SWM). There was no evidence that this was due to an attentional deficit. No other significant effects were demonstrated. Discussion: SWM is impaired in mood disorders. We found evidence for a relationship between subjective sleep disturbance and SWM impairment. Notably, this is a specific effect and not related to a generalised or attentional impairment. Therefore, poor SWM in patients with mood disorders may be related to sleep function. Conclusion: This study demonstrated a correlation between subjective sleep disturbance and poor performance on tasks of SWM in healthy subjects.